85.3k views
2 votes
Solve the following system of equations by the substitution method. 3x = y + 6 x = 2y - 1

1 Answer

4 votes

Answer:


x=(13)/(5), y= (9)/(5)

Explanation:

First Equation:

3x = y + 6

Or,

y = 3x - 6

2nd Equation:

x = 2y - 1

Lets substitute the expression for "y" from 1st equation in 2nd and solve for x:

x = 2y - 1

x = 2(3x - 6) - 1

x = 6x - 12 - 1

x = 6x - 13

5x = 13

x = 13/5

Now we can substitute this value of x into bold 1st equation and get y:

y = 3x - 6

y = 3(13/5) - 6

y = 9/5

This is the solution

User Dinorah
by
4.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.